Spiritual Accounting: The Meaning of Income in Rambu Solo' Culture in Tana Toraja Regency - Ismayanti, Ismayanti; Laekkeng, Mursalim; Zakaria, Junaiddin; Junaid, Asriani (INVOICE : JURNAL ILMU AKUNTANSI, 2024)
The purpose of this study was to determine and analyse the meaning of income in the rambu solo' culture in Tana Toraja Regency from a spiritual accounting perspective. This research uses an Interpretative Phenomenological Analysis (IPA) approach using a spiritual-religious paradigm. The data obtained came from various literature and interview sources selected based on purposive sampling, with Divine Command Theory (DCT) as the analytical knife of this research. The results of this study show that: (1) Income in the rambu solo' culture occurs due to economic activity in the frame of the principle of helping and easing each other's burdens (kasianggaran) at the time of mourning. Income is not only obtained by the to mate family but all stakeholders feel the impact of rambu solo' activities . Especially in the fields of tourism, hospitality, MSMEs, animal husbandry, village development, and Income Per Capita (IPC). (2) Income based on a non-material perspective in the frame of spiritual accounting. Based on aluk todolo belief, blessings come from titinan tallu tirindu batu lalikan for to mate and to lino. While Christianity blessings come from God alone to to lino. The benefits of the implementation of rambu solo' received by tomate are animals sacrificed as provisions for the journey to puya and become tomembali puang. Meanwhile, tolino gained peace, prosperity, increased spirit of hard work, fellowship, brotherhood, shame patriotism, honesty, mutual help, mutual love, religion and development and preservation of arts culture.